PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING UNTUK MENINGKATKAN KEMAMPUAN MENYELESAIKAN SOAL CERITA TENTANG PECAHAN PADA SISWA KELAS V SDN 1 KRAKAL TAHUN AJARAN 2015/2016 - Putra, Anjrah Setyarka (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Problem Solving Learning Model in Improving Solving Problem Ability about Fraction for the Fifth Grade Students of SD Negeri 1 Krakalin the Academic Year of 2015/2016. The objective of this research is to improve solving problem ability about fraction. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles.Each cycle consisted of planning, action, observation, and reflection.Subjects of the research were 32 students of the fifth grade of SD Negeri 1 Karakal.The results of this research show that:the application of Problem Solving learning model conducted appropriately can improve solving problem ability about fraction for the fifth grade students of SD Negeri 1 Krakal in the academic year of 2015/2016. Keywords: problem solving, essay problem, fraction